Sub-meter resolution wetland map of Hainan with detailed types from multi-source satellite imagery - Xiaohai Zhang; Jiahui Liu; Sheng Liu; Jiaju Yu; Kang Deng; Weiping Ding; Zeheng Chen; Fangyi Li (Frontiers in Marine Science, 2025)
Introduction Obtaining wetland data with high spatial accuracy and typological completeness is essential for understanding ecosystem functions, evaluating services, and informing conservation policy. However, fine-scale wetland mapping in tropical island regions remains challenging due to persistent cloud cover, image limitations, complex wetland types, and dynamic hydrology. Methods We developed a sub-meter resolution wetland mapping framework for Hainan Island, China, by integrating multi-source optical imagery (WorldView-2/3, Gaofen-1/2), dual-temporal features, and RTK-based field validation. A hierarchical classification system was designed, consisting of three major categories and 17 subcategories, aligned with Ramsar Convention criteria and adapted to island-specific conditions. Results The 2019 wetland map (3842.84 km 2 ) achieved an overall accuracy of 96.13% (Kappa = 0.95). The framework successfully identified numerous small and fragmented wetland patches (0.0004–0.08 km 2 ) that had been omitted in national wetland inventories. The results also revealed rapid artificial wetland expansion and pronounced spatial heterogeneity in natural wetlands. Discussion This study delivers a reliable high-resolution dataset and a replicable methodology for tropical island wetland mapping. The results provide a critical basis for wetland monitoring, blue carbon assessment, and ecological management, while offering a transferable framework that can be applied to other coastal and island environments.